2003
DOI: 10.1016/j.rapm.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A preoperative retrobulbar block in patients undergoing scleral buckling reduces pain, endogenous stress response, and improves vigilance

Abstract: Because the analgesic effect of the retrobulbar block was considerably longer than pharmacologically expected, the combined retrobulbar and general anesthesia "protects" against postoperative pain and is recommended for patients undergoing scleral buckling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Other authors have also demonstrated the efficacy of preemptive local anesthesia in the presence of intraoperative opioid application. 6,10,12,13 Among the different regimens examined, the application of 5 mL before surgery was clearly superior, achieving complete freedom of pain after 24 hours in all but 2 patients. Lower doses or an injection after surgery failed to achieve sufficient analgesia, whereas the injection after surgery had an overall inferior effect.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors have also demonstrated the efficacy of preemptive local anesthesia in the presence of intraoperative opioid application. 6,10,12,13 Among the different regimens examined, the application of 5 mL before surgery was clearly superior, achieving complete freedom of pain after 24 hours in all but 2 patients. Lower doses or an injection after surgery failed to achieve sufficient analgesia, whereas the injection after surgery had an overall inferior effect.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the adoption of day care units greatly increases the utilization of beds, reduces medical resources waste, and enables surgeons to perform more surgeries at a certain time [25, 26]. The administration of LA contributes to the application of day care surgery by saving operation time, lowering systemic risks of anesthetic accidents, and reducing the potential danger during recovery in comparison to GA [7, 29, 30]. Besides, patients under LA have a quick recovery postoperatively and patient comfort is increased with the use of LA [29, 31].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of LA contributes to the application of day care surgery by saving operation time, lowering systemic risks of anesthetic accidents, and reducing the potential danger during recovery in comparison to GA [7, 29, 30]. Besides, patients under LA have a quick recovery postoperatively and patient comfort is increased with the use of LA [29, 31]. Moreover, the administration of ketorolac adds to the feasibility and acceptability of day care scleral buckling surgery under LA.…”
Section: Discussionmentioning
confidence: 99%
“…In the retrobulbar approach, local anaesthetic agent is injected into the retrobulbar space, penetrating the ocular muscle cone (Vogt et al . ). A peribulbar approach is where an anaesthetic agent is injected into the extraconal orbital space and spreads by pressure and diffusion throughout this area (Gioia et al .…”
Section: Introductionmentioning
confidence: 97%